Potential mechanisms underlying CDK5 related Osteosarcoma progression. (4th May 2017) - Bao, Hang-xing; Bi, Qing; Han, Yong; Zhao, Chen; Zou, Hai
ABSTRACT: Objectives : Identification of new prognostic biomarkers and therapeutic targets is of crucial importance for patients with osteosarcoma. Cyclin-dependent kinase 5 (CDK5) is overexpressed in several tumor types. However, the exact role CDK5 plays in osteosarcoma is still unknown. Methods : In this study, we explored the association between CDK5 expression and the prognosis of osteosarcoma patients using publicly available gene expression datasets. Potential molecular mechanisms underlying its pro-malignant role in cancer progression were also discussed. Results : We demonstrated that tricarboxylic acid (TCA) cycle is activated while antigen presentation is repressed in patients with CDK5 overexpression and poor survival. This results indicated that sufficient energy production and tumor immune escape are important characteristics and potential therapeutic targets for this subgroup of osteosarcoma patients. Furthermore, several critical hub genes that are associated with CDK5 related osteosarcoma progression such as MELK were identified. Conclusion : This study discussed the pro-malignant role of CDK5 and potential mechanisms involved. Further preclinical and clinical studies to develop CDK5 based treatments are warranted.